A gradient structure enameled wire insulating paint layer and a preparation method thereof
By utilizing the gradient structure of the enameled wire insulation layer and the gradient distribution of nano-graphene oxide in epoxy resin, the problems of uneven electric field distribution and poor corona resistance of enameled wire insulation in high-frequency, high-power power systems are solved, achieving more stable electric field control and a longer service life.
Patent Information
- Application Number
- CN202611164942.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-11-03
AI Technical Summary
Existing enameled wire insulation varnishes exhibit uneven electric field distribution and poor corona resistance in high-frequency, high-power power systems, leading to a high risk of localized overheating and breakdown, and failing to effectively suppress corona phenomena.
The gradient structure enameled wire insulation layer is prepared by a thin-layer multi-pass coating process using an epoxy resin system containing different proportions of nano-graphene oxide to form a multi-layer structure, thereby optimizing the electric field distribution and corona resistance.
It significantly suppresses local electric field concentration, delays the risk of breakdown, improves the reliability of the insulation layer in high temperature and high frequency environments, is compatible with existing production lines without modification, adapts to complex voltage waveforms, and extends service life.
Smart Images

Figure CN123033808A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a gradient structure enameled wire insulation varnish layer and its preparation method, belonging to the field of electrical insulation materials and their preparation technology. Background Technology
[0002] Enameled wire is a core basic material in the electrical engineering field, mainly composed of a conductor and an insulating layer covering it. Currently, enameled copper round wire, due to its excellent conductivity and mechanical formability, is widely used in various motors (such as drive motors for new energy vehicles and industrial servo motors), power equipment (such as transformers and reactors), and precision electronic products (such as relays and solenoid valves). In these applications, the insulation performance of the enameled wire directly determines the withstand voltage rating, operational stability, and service life of the electrical equipment, and is a key factor in ensuring the safety and reliability of the equipment.
[0003] Traditional enameled wire insulation layers are mostly made by applying epoxy insulating varnish multiple times and then baking and curing. Although this type of material performs stably under normal operating conditions, with the development of power electronics technology towards higher frequencies and higher power densities, existing epoxy insulating varnishes are gradually revealing the following significant technical bottlenecks, which restrict the further improvement of the performance of high-end electrical equipment: First, the electric field distribution inside the insulating medium is uneven. Under high voltage or high frequency environment, the electric field inside the insulating layer is easy to concentrate, which leads to local overheating and breakdown. Second, the low initiation voltage of corona generation and poor corona resistance make it unable to effectively suppress local ionization, especially in high-voltage applications such as transformers and reactors, where there is a risk of premature aging and failure.
[0004] Therefore, with the development of high-frequency, high-power power systems, there is an urgent need for new insulating varnish materials with better performance and more stable structure. Summary of the Invention
[0005] To address the problems of weak electric field control capability and poor corona resistance in existing enameled wire insulation varnishes, this invention provides a gradient structure enameled wire insulation varnish layer and its preparation method.
[0006] The technical solution of this invention: One objective of this invention is to provide a gradient structure enameled wire insulating varnish layer, which is a multilayer structure prepared by a thin-layer multi-pass coating process using an epoxy resin system containing nano-graphene oxide, wherein the mass of nano-graphene oxide contained in adjacent layers is different; the thickness of the insulating varnish layer is 80~120μm.
[0007] Further specified, the thickness of each paint film is 16~24μm.
[0008] To further define, the epoxy resin system includes an epoxy resin matrix, a curing agent, an accelerator, nano-graphene oxide, and additives.
[0009] Furthermore, the epoxy resin matrix is bisphenol A epoxy resin E-51, the curing agent is methylnadic anhydride or maleic anhydride, the accelerator is imidazole, pyridine or 2-methylpyridine, and the additives are dimethylformamide, KH550 or BK333.
[0010] Furthermore, the mass ratio of epoxy resin matrix to curing agent is 100:30~130:45, the mass of accelerator is 0.01%-5% of the mass of epoxy resin matrix, the mass of nano-graphene oxide in each layer is 0~1% of the mass of epoxy resin matrix in each layer, and the mass ratio of nano-graphene oxide to additives is 1:(0.95~1.05).
[0011] Further specifying, according to the order of the insulating varnish layer from the inside out, the mass content of nano-graphene oxide in each layer is 0%, 0.25%, 0.5%, 0.75% and 1% of the mass of epoxy resin matrix in each layer.
[0012] Further specifying, according to the order of the insulating varnish layer from the inside out, the mass content of nano-graphene oxide in each layer is 0%, 1%, 0.75%, 0.5% and 0.25% of the mass of epoxy resin matrix in each layer.
[0013] Further specifying, according to the order of the insulating varnish layer from the inside out, the mass content of nano-graphene oxide in each layer is 0%, 0.25%, 1%, 0.75% and 0.5% of the mass of epoxy resin matrix in each layer.
[0014] Further specifying, according to the order of the insulating varnish layer from the inside out, the mass content of nano-graphene oxide in each layer is 0%, 0.75%, 1%, 0.25% and 0.5% of the mass of epoxy resin matrix in each layer.
[0015] The second objective of this invention is to provide a method for preparing the above-mentioned gradient structure enameled wire insulating varnish layer, the method comprising the following steps: Step 1: Dissolve the epoxy resin matrix in DMF, add nano-graphene oxide, mix evenly, and then perform vacuum distillation at -1 bar and 135°C to remove DMF. Then add curing agent and accelerator, stir evenly, and then perform gradient temperature curing treatment on the obtained adhesive to obtain self-adhesive insulating varnish. Step 2: Adjust the amount of nano-graphene oxide added in Step 1 to obtain self-adhesive insulating varnishes with different mass ratios of nano-graphene oxide. Step 3: Apply thin layers of paint to the metal wires using fine spraying equipment, and pre-cur each layer with hot air. Repeat the painting and pre-curing steps until a multi-layer structure is formed. Step 4: The multilayer structure obtained in Step 3 is cured at 100℃~200℃ for 2 hours to obtain a gradient structure enameled wire insulation layer.
[0016] Further specifying, the gradient temperature curing process in step 1 is as follows: hold at 110℃ for 1 hour, then raise the temperature to 150℃ and hold for 2 hours, and finally raise the temperature to 180℃ and hold for 3 hours.
[0017] Further specifying, the pre-curing temperature in step 3 is 80℃~100℃, and the time is 3~5min.
[0018] Beneficial effects: This invention utilizes an epoxy resin-based formulation, selects a high-molecular crosslinking modifier, and adds nano-graphene oxide as a functional modifier in extremely low proportions. It employs a thin-layer, multi-pass coating process, with pre-curing after each layer to form a multi-layered insulating structure. Finally, a post-curing treatment ensures that each layer is fully crosslinked to form a stable network structure, resulting in a novel composite structure of epoxy-based composite insulating varnish with high nonlinear coefficient and low percolation threshold. This epoxy-based composite insulating varnish exhibits nonlinear conductivity characteristics, excellent electric field distribution regulation capability, and corona resistance. Compared with existing technologies, this invention has at least the following advantages: (1) The insulating varnish layer prepared by the present invention precisely controls the dielectric constant and nonlinear coefficient of the composite insulating varnish by using nano-graphene oxide with extremely low content, optimizes the electric field distribution inside the insulating medium, significantly suppresses the problem of local electric field concentration, effectively delays the risk of partial discharge and breakdown, and solves the technical problem of weak electric field control capability and poor corona resistance of traditional insulating varnish under high voltage and high frequency environment.
[0019] (2) By constructing a gradient insulation structure, the present invention improves the adaptability of the insulation layer to complex voltage waveforms, extends the service life of the insulation system, and enhances the reliability of the material in high-temperature and high-frequency electrical equipment.
[0020] (3) The thin-layer multi-pass coating process adopted in this invention is compatible with existing continuous coating production lines for enameled wires, requires no additional equipment modification, and has good process adaptability and industrialization prospects.
[0021] (4) The gradient structure enameled wire insulation layer prepared by the present invention has wide application value in the fields of ordinary household appliances, industrial motors, transformers, automotive drive motors and power system reactors, and is expected to provide a new generation of material solutions for high-performance electromagnetic winding insulation systems. Attached Figure Description
[0022] Figure 1 TEM image of GO; Figure 2 Figures showing the changes in dielectric constant and dielectric loss of GO / EP insulating varnishes with different contents prepared for Comparative Examples 1-5. Figure 3 The nonlinear conductivity and dielectric strength variation of GO / EP insulating varnishes with different contents prepared for comparative examples 1-5 are shown in the figure. Figure 4 Comparison of dielectric and conductivity properties of insulating varnishes with different fillers prepared in Comparative Examples 6-9; Figure 5 Comparison of the electrical properties of different groups of composite insulating varnishes prepared in Examples 1-5; Figure 6 The simulation diagram shows the effect of different types of insulating varnishes prepared in Comparative Examples 1, 6-9 and Examples 1-5 on the distribution of electric field strength on the outer surface. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0024] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.
[0025] The bisphenol A epoxy resin E-51 used in the following examples was purchased from Jining Benno Biotechnology Co., Ltd.; the particle size of the nano-graphene oxide was 50~200nm; the particle size of the alumina was 80~100nm; the particle size of the silicon carbide was 5~8μm; the particle size of the zinc oxide was 0.5~0.8μm; and the particle size of the silicon dioxide was 25~35nm. Example 1 The method for preparing the gradient structure enameled wire insulation layer in this embodiment includes the following steps: Step 1: Dissolve 100g of bisphenol A epoxy resin E-51 in 0.5g of DMF, add 1g of nano-graphene oxide, mix well, and then perform vacuum distillation at -1 bar and 135℃ to remove DMF. Then add 30g of curing agent methylnadic anhydride and 0.05g of accelerator pyridine, stir well, and then perform gradient temperature curing in a benchtop vacuum drying oven. The specific process is as follows: keep at 110℃ for 1h, then raise the temperature to 150℃ and keep at 2h, and finally raise the temperature to 180℃ and keep at 3h to obtain a self-adhesive insulating varnish with a nano-graphene oxide ratio of 1, abbreviated as GO1. Step 2: Adjust the amount of nano-graphene oxide added in Step 1 to obtain a self-adhesive insulating varnish with a nano-graphene oxide content of 0.75, abbreviated as GO. 0.75 ; A self-adhesive insulating varnish with a nano-graphene oxide content of 0.5%, abbreviated as GO 0.5 ; A self-adhesive insulating varnish with a nano-graphene oxide content of 0.25%, abbreviated as GO 0.25 ; A self-adhesive insulating varnish with a nano-graphene oxide content of 0, abbreviated as GO0; Step 3: Apply thin, multi-coat paint to the surface of the metal conductor using a fine spraying device. Each coat should be approximately 15μm thick. After each coat, pre-curing is performed at 80℃ with hot air for 5 minutes. Repeat the above steps, following steps GO0 and GO0. 0.25 GO 0.5 GO 0.75 The paint and pre-curing process is carried out in the order of GO1 from the inside out to obtain a multi-layer structure; Step 4: The multilayer structure obtained in Step 3 is cured at 120°C for 2 hours to obtain a gradient structure enameled wire insulation layer, named Group A.
[0026] Example 2 The difference between this embodiment and embodiment 1 is that in step 3, GO0, GO1, GO... 0.75 GO 0.5 And GO0. 25 The painting and pre-curing processes are carried out from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, resulting in a gradient structure enameled wire insulation layer, which is named Group B.
[0027] Example 3 The difference between this embodiment and embodiment 1 is that in step 3, according to GO0, GO 0.25 GO1 GO 0.75 The coating and pre-curing process is carried out in the order of GO0.5 from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, resulting in a gradient structure enameled wire insulation layer, which is named Group C.
[0028] Example 4 The difference between this embodiment and embodiment 1 is that in step 3, according to GO0, GO 0.75 GO1 GO 0.25 The coating and pre-curing process is carried out in the order of GO0.5 from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, resulting in a gradient structure enameled wire insulation layer, named Group D.
[0029] Comparative Example 1 The difference between this comparative example and Example 1 is that in step 3, the coating and pre-curing process is carried out from the inside out in the order of GO0, GO0, GO0, GO0 and GO0 to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, and the enameled wire insulation varnish layer is obtained, named EP.
[0030] Comparative Example 2 The difference between this comparative example and Example 1 is that in step 3, according to GO... 0.25 GO 0.25 GO 0.25 GO 0.25 and GO 0.25 The painting and pre-curing processes are carried out from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, resulting in an enameled wire insulating varnish layer named GO. 0.25 / EP.
[0031] Comparative Example 3 The difference between this comparative example and Example 1 is that in step 3, according to GO... 0.5 GO 0.5 GO 0.5 GO 0.5 and GO 0.5 The painting and pre-curing processes are carried out from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, resulting in an enameled wire insulating varnish layer named GO. 0.5 / EP.
[0032] Comparative Example 4 The difference between this comparative example and Example 1 is that in step 3, according to GO... 0.75 GO 0.75 GO 0.75 GO 0.75 and GO 0.75 The painting and pre-curing processes are carried out from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, resulting in an enameled wire insulating varnish layer named GO. 0.75 / EP.
[0033] Comparative Example 5 The difference between this comparative example and Example 1 is that in step 3, the coating and pre-curing process is carried out from the inside out in the order of GO1, GO1, GO1, GO1 and GO1 to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, and the enameled wire insulation varnish layer is obtained, named GO1 / EP.
[0034] Comparative Example 6 The difference between this comparative example and Example 1 is that in step 1, 20g of alumina was used instead of 1g of nano-graphene oxide to obtain a self-adhesive insulating varnish, abbreviated as (Al2O3). 20wt% In step 3, according to (Al2O3) 20wt% (Al2O3) 20wt% (Al2O3) 20wt% (Al2O3) 20wt% and (Al2O3) 20wt% The painting and pre-curing processes are carried out from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, resulting in an enameled wire insulating varnish layer named Al2O3 / EP.
[0035] Comparative Example 7 The difference between this comparative example and Example 1 is that in step 1, 15g of silicon carbide was used instead of 1g of nano-graphene oxide to obtain a self-adhesive insulating varnish, abbreviated as (SiC). 15wt% In step 3, according to (SiC) 15wt% (SiC) 15wt% (SiC) 15wt% (SiC) 15wt% and (SiC) 15wt% The coating and pre-curing process is carried out from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, resulting in an enameled wire insulating varnish layer named SiC / EP.
[0036] Comparative Example 8 The difference between this comparative example and Example 1 is that in step 1, 10g of zinc oxide was used instead of 1g of nano-graphene oxide to obtain a self-adhesive insulating varnish, abbreviated as (ZnO). 10wt% In step 3, according to (ZnO) 10wt% (ZnO) 10wt% (ZnO) 10wt% (ZnO) 10wt% and (ZnO) 10wt% The coating and pre-curing process is carried out from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, resulting in an enameled wire insulating varnish layer named ZnO / EP.
[0037] Comparative Example 9 The difference between this comparative example and Example 1 is that in step 1, 10g of silicon dioxide was used instead of 1g of nano-graphene oxide to obtain a self-adhesive insulating varnish, abbreviated as (SiO2). 10wt% In step 3, according to (SiO2) 10wt% (SiO2) 10wt% (SiO2) 10wt% (SiO2)10wt% and (SiO2) 10wt% The coating and pre-curing process is carried out from the inside out to obtain a multi-layer structure. The remaining process steps and parameter settings are the same as in Example 1, and the enameled wire insulation varnish layer is obtained, named SiO2 / EP.
[0038] Example of effect The properties of the insulating varnish layers prepared in Examples 1-4 and Comparative Examples 1-9 were characterized, and the test results are as follows: (1) Figure 1 This is a TEM image of nano-graphene oxide. The image reveals a large-area, nearly transparent sheet-like structure, exhibiting typical graphene sheet characteristics. The darker-colored wrinkled areas represent the folding and stacking of graphene sheets. No obvious pores or defects were observed, and the overall continuity of the sheets is good, indicating that the graphene sheets possess high structural integrity.
[0039] (2) Figure 2 Figure (a) shows the frequency-dependent dielectric constant of the GO / EP insulating varnish. With increasing GO content, the overall dielectric constant of the composite material decreases, exhibiting typical interfacial polarization relaxation characteristics. At low frequencies, space charge accumulates at the GO-EP interface, forming interfacial polarization; as the frequency increases, charge migration and dipole orientation gradually lag behind the applied electric field, the polarization contribution weakens, and the dielectric constant decreases. Among these, GO... 0.5 / EP at 10 0 Hz-10 6 It exhibits the best dielectric stability in the Hz range, with the dielectric constant remaining between 4.2 and 5.0, and the variation is significantly smaller than that of pure EP and GO. 0.75 / EP system. This is mainly attributed to the appropriate amount of GO uniformly dispersed in the matrix, which enhances the interfacial constraint effect, suppresses low-frequency space charge polarization, and at the same time constructs a stable microcapacitor network, thereby achieving synergistic optimization of dielectric properties over a wide frequency range. Figure 2 (b) represents dielectric loss. In the low-frequency range, conductivity and interfacial polarization loss are the main components, while in the high-frequency range, the loss increases rapidly due to dipole relaxation, reaching 10. 2 ~10 3 A loss valley forms near Hz. Due to the filler agglomeration effect, the polarization sites of GO1 / EP are limited, resulting in a lower dielectric constant and the lowest loss across the entire frequency range compared to pure EP. This anomalous behavior is not due to performance optimization, but rather to the high GO content agglomeration restricting carrier migration and interfacial polarization. In contrast, samples with medium to low GO content (0.25~0.5wt.%) have a higher dielectric constant in the low-frequency range due to interfacial polarization, but their high-frequency loss increase is relatively controllable.
[0040] (3) Figure 3 This represents the effect of GO on the electrical conductivity and dielectric strength of insulating varnish. Figure (a) shows the effect on the dielectric strength of the insulating varnish under linear coordinates.J - E Characteristics, (b) are in double logarithmic coordinates J - E Characteristic, (c) is J / E 2 -1 / E Curve (d) shows the change in dielectric strength of GO / EP insulating varnish. From (a), it can be seen that the current density of the insulating varnishes prepared in Comparative Examples 1-5 does not change significantly with increasing electric field strength. When the electric field strength exceeds 12 kV / mm, the components with GO addition greater than 0.5 wt.% show a slight increase in current density, indicating that when the GO addition exceeds 0.5 wt.%, the insulating varnish exhibits nonlinear characteristics, most notably in GO1 / EP insulating varnish. Linear fitting of Figure (a) yields Figure (b), dividing the current density under different field strengths into ohmic and non-ohmic regions. It can be seen that the slope of the current density in these two stages for different insulating varnishes is positively correlated with the applied field strength. The slope of the fitted equation is lower in the low field strength region, while when the field strength suddenly reaches a certain threshold, the current density of the insulating varnish enters the next stage with a sharp increase in slope. To verify that the relationship between current density and electric field strength is related to the tunneling effect, the ln... J / E 2 With 1 / E The relationship curve (c) illustrates that under high electric field strength, the tunneling effect is the main reason for the conductivity mechanism inside the insulating varnish. However, the electron tunneling effect is usually only at 100 kV·mm. -1This occurs under high electric fields. Because GO has an irregular shape, sharp corners, and very small distances between GO sheets (typically at the nanometer level), when the self-adhesive insulating varnish is subjected to an external electric field, the enhancement of the local electric field leads to a sharp increase in electrical stress between adjacent GO sheets, forming discontinuous conductive channels or conductive islands. When electrons gain sufficient energy, quantum effects are significantly enhanced, increasing electron wave properties and tunneling probability. GO can form multiple conductive pathways in the polymer matrix. Simultaneously, the electron tunneling barrier is further reduced, allowing the tunneling effect to occur even in low electric field environments. (d) shows the change in dielectric strength of EP insulating varnish with different GO contents. With increasing GO content, the dielectric strength first increases and then decreases, reaching a maximum of 21.89 kV / mm when the GO content is 0.5 wt.%, which is 1.158 times that of pure epoxy resin. GO sheets are uniformly dispersed in the EP matrix. On the one hand, they trap space charge through interface traps, reducing electric field distortion; on the other hand, they form a barrier structure, extending the breakdown path and thus improving dielectric strength. When the GO content exceeds 0.5 wt.%, the filler is prone to agglomeration, introducing interface defects and local conductive pathways, leading to increased electric field concentration and a significant decrease in dielectric strength.
[0041] (4) Figure 4 The dielectric and conductivity properties of the insulating varnishes prepared in Examples 6-9 are shown in Figures (a) and (b) respectively. Figure (c) shows the dielectric constant variation of the insulating varnishes with different fillers, (d) shows the dielectric loss variation of the insulating varnishes with different fillers, (c) shows the dielectric strength variation of the insulating varnishes with different fillers, and (d) shows the nonlinear conductivity characteristics of the insulating varnishes with different fillers in logarithmic coordinates. J - E Characteristics. Due to the high intrinsic dielectric constant and strong interfacial polarization effect of SiC and ZnO, their composite system exhibits a higher dielectric constant; while the dielectric enhancement effect of Al2O3 and SiO2 is relatively limited. Compared with sheet-like GO, spherical inorganic fillers maintain better stability of dielectric constant within the test frequency band. (b) The differences in dielectric loss of each filler system in the figure are mainly due to the differences in filler morphology, surface defects, insulation and conductivity characteristics and interfacial bonding state. SiO2 has the highest overall loss due to its many surface defects, poor interfacial compatibility, significant space charge accumulation and conductivity loss; two-dimensional sheet-like GO can optimize the interfacial structure, suppress charge migration and polarization relaxation, and minimize the dielectric loss of composite materials; while ZnO, Al2O3, and SiC particle fillers have no obvious defects and strong loss effects, the interfacial effect and carrier loss are relatively mild and balanced, and multiple loss mechanisms counterbalance each other, ultimately showing a moderate dielectric loss level. (c) Figure GO 0.5The overall dielectric strength of the / EP insulating varnish is 25kV / mm. Among the insulating varnishes with different types of fillers, Al2O3 modified epoxy resin has the best breakdown performance. GO, SiC, and ZnO modified insulating varnishes have similar breakdown resistance levels. SiO2 filler has poor adhesion to the matrix interface, is prone to generating microscopic air gap defects, and has a lower dielectric strength. In Figure (d), SiO2 and Al2O3 are wide-bandgap insulating fillers with few intrinsic charge carriers and deep interface traps that can bind space charges. They have low leakage current and weak nonlinear conductance under both high and low fields, and outstanding high-voltage insulation stability. SiC and ZnO have intrinsic charge carriers and tunable grain boundary barriers, and have the ability to self-homogenize electric fields. Among them, the conductance of SiC increases gradually with the field strength, while the grain boundary barrier of ZnO is easily broken down under high fields, and the leakage current surges more. GO high-conductivity sheets have unique advantages. Under low electric fields, the sheets are separated by epoxy groups and the interface traps effectively bind charge carriers, resulting in the lowest initial leakage current in the entire system. The low-voltage insulation loss is far better than other fillers. At the same time, its nonlinear response threshold is lower, and the characteristic of rapid conductance increase under high fields can quickly divert local concentrated electric fields. The electric field control response sensitivity is significantly higher than that of SiC and ZnO.
[0042] (5) Figure 5 The graph shows the influence of different groups of composite insulating varnishes on dielectric properties under 50Hz operating conditions. The overall values of dielectric constant, dielectric loss, and dielectric strength for each group show relatively small fluctuations. Group A employs a high-content GO layer external structure, where numerous phase interfaces on the surface induce strong interfacial polarization, resulting in relatively high dielectric constant and dielectric loss compared to other groups. The outer GO layer acts as a charge trap, capturing charge carriers and suppressing breakdown channel formation, thus achieving the optimal breakdown field strength. Group B features a high-content GO layer internal structure. Based on COMSOL electric field simulation results, this arrangement effectively homogenizes the electric field according to the high dielectric properties of GO and does not form a continuous conductive network, leading to a reduction in dielectric loss. However, the high concentration of GO in the inner layer is prone to aggregation and structural defects. Even with a lower overall electric field level, these defective areas become weak points for breakdown, resulting in a slight decrease in macroscopic dielectric strength. After optimizing the gradient layers and filler distribution, Group C shows improved interfacial conditions and filler dispersion, with all performance indicators slightly improving compared to Group B, exhibiting a more stable and balanced overall performance. Group D's rational layered arrangement further suppresses interfacial polarization and relaxation loss, achieving the lowest relative permittivity and dielectric loss among the four groups. Simultaneously, it effectively avoids filler agglomeration and defect concentration, achieving a uniform electric field distribution while maintaining a high breakdown field strength. Figure 5As shown in Figure (d), the nonlinear conductivity parameters of samples with different gradient structures are relatively similar. Adjusting the gradient structure alters the spatial distribution and interface state of GO, thus affecting the local electric field distribution and charge migration paths. Specifically, in group A, the high GO content in the outer layer more readily induces interface polarization and charge accumulation, while the optimized gradient structure helps to reduce local field distortion and make carrier transport more uniform. With increasing electric field, carriers gradually overcome the interface barrier, enhancing field-induced tunneling and hopping conduction mechanisms. All groups exhibit similar nonlinear growth trends, indicating that the gradient structure primarily optimizes performance by controlling the electric field distribution and charge transport behavior.
[0043] (6) Figure 6 The diagram shows the simulation effects of the external surface electric field distribution on the insulating varnish layers prepared in Examples 1-4 and Comparative Examples 6-9. Where a represents EP, b represents group A, c represents group B, d represents group C, e represents group D, f represents SiO2 / EP, g represents SiC / EP, h represents Al2O3 / EP, and i represents ZnO / EP. COMSOL simulation results show that the nonlinear threshold electric field of the gradient structure insulating varnish layers in groups A, B, C, and D is concentrated around 15.80 kV / mm, while the nonlinear threshold electric field of ZnO / EP, Al2O3 / EP, SiC / EP, and SiO2 / EP insulating varnishes are 16.575 kV / mm, 15.8443 kV / mm, 16.5656 kV / mm, and 16.4928 kV / mm, respectively. j represents GO. 0.25 / EP, k is GO 0.5 / EP、l for GO 0.75 / EP and m represent the COMSOL nonlinear threshold field simulation results for GO1 / EP insulating varnish. Overall, the threshold field strength of the gradient GO / EP system is lower than that of the composite systems with different fillers and without gradient structures, indicating that it is more likely to trigger nonlinear conductivity under an applied electric field. When the GO content is distributed according to group B, the system exhibits the lowest nonlinear threshold field strength (15.8013 kV / mm). The nonlinear responses of the ZnO / EP, Al2O3 / EP, SiC / EP, and SiO2 / EP systems mainly originate from the large number of interface regions formed between the filler and the epoxy matrix. Under the action of an applied electric field, the space charge accumulated at the interface induces interface polarization, thereby changing the local electric field distribution. However, since the filler is relatively uniformly distributed throughout the coating, the electric field modulation effect is mainly limited to the micro-interface scale, and its conductivity change and electric field reconstruction ability are limited. Therefore, a higher applied electric field is required to achieve the triggering condition for nonlinear conductivity. The gradient structure insulating varnish not only has the GO / EP interface polarization effect, but also constructs a conductivity gradient that varies continuously along the thickness direction. Under an applied electric field, the conductive network of the high-GO content layer responds to the electric field first, while the low-GO content layer maintains higher insulation performance. As the electric field intensifies, the difference in interlayer conductivity leads to a redistribution of the electric field, causing local regions to reach nonlinear conductivity conditions first, thus triggering conductivity transitions earlier and reducing the threshold field strength. The interlayer electric field segmentation effect can induce electric field reconstruction and suppress local field strength concentration. The synergistic effect of conductive network modulation, interface polarization, and electric field segmentation gives the gradient GO / EP system a lower nonlinear threshold field strength and a better field strength homogenization capability.
[0044] (7) Table 1 shows the electrical performance parameters of composite materials with high filler content and nonlinear conductivity after verification. Most systems in the table require more than 10 wt.% filler to achieve significant nonlinearity. High filler content can also easily lead to problems such as increased matrix defects, decreased interfacial compatibility, and deterioration of breakdown strength. The breakdown strength of high filler content systems often decreases by more than 30% and the dielectric constant increases by more than 50%. The gradient-distributed GO filler has no continuous conductive path in the epoxy matrix. Under low electric field, a large number of deep traps are formed at the interface between the resin matrix and the filler, which effectively binds the charge carriers. Therefore, the dielectric constant of this system is only 3.9~4.15, the low-voltage leakage current is extremely low, and the steady-state insulation loss is excellent. Its threshold electric field is stable at 15.80 kV / mm, which is lower than that of various inorganic oxides and semiconductor fillers. Under medium field strength, the trap charge de-trapping and interlayer tunneling effect are activated, and nonlinear conductivity is successfully generated to alleviate the local distortion electric field. The gradient structure disperses the GO layers. It retains the strong nonlinear response characteristics of graphene while avoiding the problem of instantaneous conduction of conductive channels and drastic current changes in uniformly doped GO under high fields. The breakdown strength is maintained at a high level of 25.4~25.9kV / mm, and the withstand voltage performance is stable. At the same time, by adjusting the GO gradient arrangement, the interface trap density and the interlayer spacing can be changed, and the threshold field and dielectric properties can be slightly controlled. Compared with SiO2 and Al2O3, it has a stronger nonlinear response, and compared with SiC and ZnO, it has a lower start-up field, taking into account the dual advantages of steady-state insulation and high-voltage self-averaging field.
[0045] Table 1 Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.
Claims
1. A gradient structure enameled wire insulating varnish layer, characterized in that, The insulating varnish layer is a multi-layer structure prepared by an epoxy resin system containing nano-graphene oxide through a thin-layer multi-pass coating process, and the mass of nano-graphene oxide contained in adjacent layers is different; the thickness of the insulating varnish layer is 80~120μm.
2. The gradient structure enameled wire insulating varnish layer according to claim 1, characterized in that, The epoxy resin system includes an epoxy resin matrix, curing agent, accelerator, nano-graphene oxide, and additives.
3. The gradient structure enameled wire insulating varnish layer according to claim 2, characterized in that, The epoxy resin matrix is bisphenol A epoxy resin E-51, the curing agent is methylnadic anhydride or maleic anhydride, the accelerator is imidazole, pyridine or 2-methylpyridine, and the additives are dimethylformamide, KH550 or BK333. The mass ratio of epoxy resin matrix to curing agent is 100:30~130:45, the mass of accelerator is 0.01%-5% of the mass of epoxy resin matrix, the mass of nano-graphene oxide in each layer is 0~1% of the mass of epoxy resin matrix in each layer, and the mass ratio of nano-graphene oxide to additives is 1:(0.95~1.05).
4. The gradient structure enameled wire insulating varnish layer according to claim 1, characterized in that, According to the order of the insulating varnish layers from the inside to the outside, the mass content of nano-graphene oxide in each layer is 0%, 0.25%, 0.5%, 0.75% and 1% of the mass of epoxy resin matrix in each layer.
5. The gradient structure enameled wire insulating varnish layer according to claim 1, characterized in that, According to the order of the insulating varnish layers from the inside to the outside, the mass content of nano-graphene oxide in each layer is 0%, 1%, 0.75%, 0.5% and 0.25% of the mass of epoxy resin matrix in each layer.
6. The gradient structure enameled wire insulating layer according to claim 1, characterized in that, According to the order of the insulating varnish layers from the inside to the outside, the mass content of nano-graphene oxide in each layer is 0%, 0.25%, 1%, 0.75% and 0.5% of the mass of epoxy resin matrix in each layer.
7. The gradient structure enameled wire insulating varnish layer according to claim 1, characterized in that, According to the order of the insulating varnish layers from the inside to the outside, the mass content of nano-graphene oxide in each layer is 0%, 0.75%, 1%, 0.25% and 0.5% of the mass of epoxy resin matrix in each layer.
8. A method for preparing a gradient structure enameled wire insulating varnish layer according to any one of claims 1 to 7, characterized in that, include: Step 1: Dissolve the epoxy resin matrix in DMF, add nano-graphene oxide, mix evenly, and then perform vacuum distillation at -1 bar and 135°C to remove DMF. Then add curing agent and accelerator, stir evenly, and then perform gradient temperature curing treatment on the obtained adhesive to obtain self-adhesive insulating varnish. Step 2: Adjust the amount of nano-graphene oxide added in Step 1 to obtain self-adhesive insulating varnishes with different mass ratios of nano-graphene oxide. Step 3: Apply thin layers of paint to the metal wires using fine spraying equipment, and pre-cur each layer with hot air. Repeat the painting and pre-curing steps until a multi-layer structure is formed. Step 4: The multilayer structure obtained in Step 3 is cured at 100℃~200℃ for 2 hours to obtain a gradient structure enameled wire insulation layer.
9. The method for preparing the gradient structure enameled wire insulation layer according to claim 8, characterized in that, The gradient temperature curing process in step 1 is as follows: hold at 110℃ for 1 hour, then raise the temperature to 150℃ and hold for 2 hours, and finally raise the temperature to 180℃ and hold for 3 hours.
10. The method for preparing the gradient structure enameled wire insulation layer according to claim 8, characterized in that, In step 3, the pre-curing temperature is 80℃~100℃ and the time is 3~5min.
